Incorporating Pd(OAc)2 on Imine Functionalized Microporous Covalent Organic Frameworks: A Stable and Efficient Heterogeneous Catalyst for Suzuki‐Miyaura Coupling in Aqueous Medium. Issue 3 (24th January 2017) - Sadhasivam, Velu; Balasaravanan, Rajendiran; Chithiraikumar, Chinnadurai; Siva, Ayyanar
Abstract: Imine‐based microporous covalent organic frameworks, TATAE were synthesized from condensation of 4, 4′, 4"‐(1, 3, 5‐triazine‐2, 4, 6‐triyl)tribenzaldehyde and 1, 4‐diaminobenzene, followed by Pd(OAc)2 was incorporated on TATAE (Pd/TATAE). The as‐synthesized Pd/TATAE was thoroughly characterized by Fourier Transform‐Infrared Spectroscopy, 13 C CP‐MAS solid state nuclear magnetic resonance, powder X‐ray diffraction, X‐ray photoelectron spectroscopy, thermo gravimetric analysis, scanning electron microscopy and transmission electron microscopy. The Pd/TATAE was employed as a solid catalyst for Suzuki‐Miyaura coupling reactions in an environmentally benign water medium at room temperature, which exhibited a good catalytic activity with excellent yield. In addition, the heterogeneous nature of the catalyst was checked by Shelton test, this catalyst can be recycled more than four times with only a minor loss of its catalytic activity. Abstract : We reported the reusable Pd/TATAE catalyst and their catalytic efficiencies is measured by the Suzuki‐Miyaura coupling reaction in an environmentally benign aqueous medium at room temperature with very good yield.